Association of Microalbuminuria and Renal Function Tests Parameters in Type 2 Diabetes Mellitus - Yadav, Nirdhan; Marasini, Surendra; Gupta, Suprita; Sah, Sanjay Kumar; Jha, Amit Chandra; Sah, Rohit; Yadav, Tapeshwar (Nepal Journal of Health Sciences, 2025)
Introduction: Type 2 diabetes mellitus, a metabolic disorder with an increasing global prevalence frequently results in chronic complications like diabetic nephropathy. Microalbuminuria is an early indicator of renal damage and glycemic factors are important for managing diabetes mellitus. Objective: This study was carried to find out the urinary microalbumin and renal function test parameters in type 2 diabetes mellitus patients. Methods: An analytical cross-sectional study was conducted over four months (March to June 2025) at the National Medical College. A total of 300 T2 diabetes mellitus patients were enrolled. Data on FBS, PPBS, HbA1C, serum urea, creatinine, sodium, potassium, and urinary microalbumin were collected and analyzed using SPSS 22. Pearson’s correlation, independent t-test, Smirnov Kolmogorov test and Mann Whitney U test, were applied where appropriate, with p<0.05 considered statistically significant. Results: Poor glycemic control was evident with mean FBS of 193.36 ± 74.86 mg/dL, PPBS of 305.70 ± 87.78 mg/dL, and HbA1C of 8.48 ± 1.84%. Renal function parameters showed elevated urea (66.45 ± 58.39 mg/dL) and creatinine (2.04 ± 1.39 mg/dL). Microalbuminuria was present in 23% and macroalbuminuria in another 13.3% of patients. Strong positive correlations were found between microalbumin and serum urea (r=0.67), creatinine (r=0.62), HbA1C (r=0.17), FBS (r=0.24), PPBS (r=0.21) potassium (r=0.49), and a negative correlation with sodium (r= -0.39) all of which were statistically significant (p < 0.01). Conclusions: The study concluded there is a significant association of urinary microalbuminuria and persistent proteinuria as well as dera ngements in the parameters of renal function test in the type 2 diabetic patients.